Economic viability of production of kokum (Garcinia indica Choicy) in Maharashtra, India - S R Torane, P J Kshirsagar, J M Talathi, H K Patil (Journal of Spices and Aromatic Crops, 2010)
Financial feasibility analysis of capital investment in kokum (Garcinia indica) in South Konkan(Sindhudurg and Ratnagiri districts in Maharashtra) revealed profitability of the enterprise.The initial investment for establishing orchards raised from seedlings and grafts were Rs.38,877 ha-1 and Rs. 69,196 ha-1, respectively. The total cost of production and gross returnswere Rs. 26,417 ha-1 and Rs. 42,820 ha-1 and Rs. 44,931 ha-1 and Rs. 45,572 ha-1, respectively fororchards raised from seedlings and grafts, with a benefit : cost ratio of 1.11 and 1.70,respectively. The net present value for both the types of orchards were positive with a payback period of 7-8 years.